Prevalence of Post-intensive care syndrome among intensive care unit-survivors and its association with intensive care unit length of stay: Systematic review and meta-analysis - Temesgen Ayenew; Menberu Gete; Mihretie Gedfew; Addisu Getie; Abebe Dilie Afenigus; Afework Edmealem; Haile Amha; Girma Alem; Bekele Getenet Tiruneh; Mengistu Abebe Messelu (PLoS ONE, 2025)
Background Post-intensive Care Syndrome (PICS) is defined as various physical, psychological, and cognitive, impairments that can arise during an ICU stay, continue after leaving the ICU, or even persist following hospital discharge. It impacts both patients and their family’s quality of life. Various primary studies worldwide have reported prevalence of PICS among ICU survivors. However, these studies exhibit inconsistency and wide variations. Therefore, this systematic review and meta-analysis aimed to estimate the pooled prevalence of post intensive care syndrome among intensive care unit survivors along with its association with ICU length of stay. Methods We used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 checklist for this review. We searched PubMed/Medline, CINHAL, Embase, and Google scholar to retrieve articles. The Newcastle Ottawa Scale (NOS) was used for quality assessment of articles. The random effects model with I-squared test was used to estimate the prevalence of PICS and its association with ICU length of stay. To identify the source of heterogeneity within the included studies, meta-regression and subgroup analysis were used. We employed Egger’s regression test and funnel plots for assessing publication bias. STATA version 17.0 software was used for all statistical analyses. A p-value of < 0.05 with 95% confidence interval was used declare statistically significant. Results A total of 19 articles with a population of 10179 ICU-survivors were included in this review. The pooled prevalence of PICS was found to be 54.35% (95% CI = 45.54, 63.15). In sub-group analysis by region, the highest prevalence was observed in studies done in south and north America with overall prevalence of 61.95% (95% CI = 28.33, 95.62). Among the three domains of PICS (physical, cognitive and mental domains), the highest prevalence score was observed in the physical domain with overall prevalence of 45.99% (95% CI = 34.66, 57.31). In this meta-analysis, those patients who stayed more than four days in the ICU were 1.207 [95% CI = 1.119, 1.295] times more likely to develop at least one among the three domains of PICS in the post-intensive care period than their counterparts. Conclusion This systematic review and meta-analysis demonstrate a high prevalence of PICS among ICU survivors, and highlight the significant association between ICU length of stay and the development of PICS. These findings underscore the need for targeted interventions to mitigate the long-term effects of critical illness, particularly for patients with prolonged ICU stays.